O ator e o curinga no teatro de Augusto Boal: do Teatro de Arena de São Paulo ao Centro de Teatro do Oprimido-Rio (1956-1989) - Fiuza, Sandra Alves (2021)
The purpose of this thesis is to analyze the actor and the joker in the trajectory of the theatrologist Augusto Boal from a historical approach. The main goal is to understand the differences and traces of continuity between the work of the actor, the joker-actor (the actor disconnection from the character) and the narrator joker of Arena Theater of São Paulo, and also between them and the joker from the Theater of the Oppressed. The main argument is that the actor’s training and work experiences within a specific collective work organization in the Arena Theater and the later dilution and popularization of the director's activity in the Theater of the Oppressed practices were respectively condensed in the joker-actor from the Arena Theater and the joker from the Theater of the Oppressed. The understanding of the movements made towards the non-specialization of the actor’s activity in Boal’s theatrical practice is a significant part of this thesis’s analyses. Through the reflections made by the participants of the Arena Theater of São Paulo about their work, it seeks to highlights the oppositional practices regarding the theater actor — from star system — and the performing style of the Brazilian Comedy Theater (TBC). By following the thread of the “selective” incorporations in the constitution of the actor’s performance at the theatrical political engagement of the 1960s, this thesis attempts to present a dialogue between the compère actor, a teatro de revista convention; the narrator, the Brazilian North-eastern pamphlets poet singer (cantador de folhetos); and the Brechtian actor, who presents the character on stage, acting as a narrator/commentator. In addition, this thesis interprets the memories of amateur actors, cultural animators, and jokers from the Theater of the Oppressed about their work experiences during their participation in the Brazilian Popular Theater Factory project (Fábrica de Teatro Popular), in 1986, and in the foundation process of the Theater of the Oppressed Centre in Rio de Janeiro, in 1989, and seek to understand these artists’ acting, and the political theater new configurations practiced by Boal and his troupe during redemocratization in the 1980s.